PLATELET BLOOD CONCENTRATE IN RECONSTRUCTIVE SURGERY OF TENDONS (EXPERIMENTAL PART) - Панов, Алексей Александрович; Панова, Анна Сергеевна; Бондарев, Олег Иванович; Азаров, Павел Алексеевич (Medicine in Kuzbass, 2019)
The article presents experimental studies on the strength, clinical and histological research of the tendon-muscle complex during the restoration of enthesis with anchors, intra-trunk reinforcement with super-elastic titanium nickelide implants and the use of autologous blood platelet concentrates. Autologous blood platelet concentrates were used to treat the implant, replace the tendon defect and heal the dehiscence of postoperative wounds. Subject of the study – reconstructive interventions in the tendon-muscular complex. Purpose of the study. Assess the strength of intact enthesis and the enthesis restored with different anchors. Assess the strength of the rabbit tendon after intra-trunk reinforcement with super-elastic implants in combination with autologous blood platelet concentrate. Assess the healing of canine tendon when using autologous blood platelet concentrate. Research methods. Strength tests of cadaver and calf tendons. Clinical trials on rabbits and dogs. Strength tests of rabbit tendons. Histological study of canine tendon regenerates. Clinical observation of postoperative wound dehiscence. Main results. The strength of intact entheses and the strength of the entheses restored by anchors were determined. The fixing ability of different types of anchors was determined. The strength of rabbit tendons after intra-trunk grafting by an ultra-elastic titanium nickelide implant in combination with an autologous blood platelet concentrate compared with the isolated use of an ultra-elastic titanium nickelide implant was evaluated and determined. The histological picture of the canine tendon regenerate after replacement of the defect with a suture and combination of the suture with autoblood platelet concentrate was compared. The results of treatment of postoperative wound dehiscence with platelet concentrate of autologous blood and Hydrosorb Hartmann gel were evaluated. The scope of their application. Reconstructive implantology of the tendon-muscular complex, restoration of tendon enthesis, intra-trunk tendon grafting, replacement of tendon defect, treatment of postoperative wounds dehiscence. Conclusions: 1. The strength of intact enthesis is significantly higher than that of the restored one. It is advisable to reinstall the tendon and recreate the enthesis with a complex of bioinert material and autologous material. 2. The fixing strength of a cylindrical anchor is higher than that of a conical one, while the installation of a conical anchor is less traumatic and invasive. 3. The strength of a rabbit tendon with intra-trunk reinforcement with super-elastic titanium nickelide implant is lower than that with a combination of super-elastic titanium nickelide and autologous blood platelet concentrate. 4. Restoration of a tendon defect in dogs with suture and autologous blood platelet concentrate effects in more vascular regeneration than restoration with only one suture. 5. The terms for the healing of postoperative wounds dehiscence during treatment with autologous blood platelet concentrate are shorter than those with Hydrosorb Hartmann gel. Conclusion. The combination of bioinert implants with autologous blood platelet concentrates makes restoration of the tendon-muscle complex more reliable, while the possibility of preparing multi-component concentrates of different consistency, from liquid to gel, gives versatility to the method.